2022
DOI: 10.1021/acs.jafc.2c04335
|View full text |Cite
|
Sign up to set email alerts
|

Two Odorant-Binding Proteins Involved in the Recognition of Sex Pheromones in Spodoptera litura Larvae

Abstract: Usually, the recognition of sex pheromone signals is restricted to adult moths. Here, our behavioral assay showed that fourth-instar Spodoptera litura larvae are attracted to cabbage laced with minor sex pheromones Z9,E12-tetradecadienyl acetate (Z9,E12-14:Ac) or Z9-tetradecenyl acetate (Z9-14:Ac). Seven odorant-binding proteins (OBPs) were upregulated after exposure to Z9,E12-14:Ac, and one OBP was upregulated after exposure to Z9-14:Ac. Fluorescence competitive binding assays showed that GOBP2 and OBP7 bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 47 publications
(90 reference statements)
0
20
0
Order By: Relevance
“…RNAi is a reliable technology currently used to explore the exact physiological function of key genes in living insects. Recently, it has been successfully applied in a variety of noctuid pests by injecting siRNA into the body, such as Spodoptera litura 50 and Mythimna separata. 51 We injected siCSP2 into male A. lepigone, and the silencing rate 24 h after treatment was 98.29%, but it has no effect on the expression level of other ten olfactory genes in male moths, indicating that we successfully knockdown AlepCSP2 to a large extent, and siCSP2 can target the silencing of target gene expression without affecting other olfactory genes.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAi is a reliable technology currently used to explore the exact physiological function of key genes in living insects. Recently, it has been successfully applied in a variety of noctuid pests by injecting siRNA into the body, such as Spodoptera litura 50 and Mythimna separata. 51 We injected siCSP2 into male A. lepigone, and the silencing rate 24 h after treatment was 98.29%, but it has no effect on the expression level of other ten olfactory genes in male moths, indicating that we successfully knockdown AlepCSP2 to a large extent, and siCSP2 can target the silencing of target gene expression without affecting other olfactory genes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…RNAi is a reliable technology currently used to explore the exact physiological function of key genes in living insects. Recently, it has been successfully applied in a variety of noctuid pests by injecting siRNA into the body, such as Spodoptera litura and Mythimna separata . We injected siCSP2 into male A.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on Spodoptera OBPs provides a blueprint for the prediction of SlitOBP ligands based on the interaction of phylogeny and chemical structure. For example, larval SlitGOBP 2 of S. litura have been reported to function in sex pheromone recognition [ 83 ]. In the same species, OBP 11 displays strong binding with sex pheromones [ 84 ] and CSP 8 can bind with the oviposition deterrent chemical rhodojaponin III [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…12,22 Some studies reported that larvae can recognize certain pheromones, 34 even sexual ones. 35 However, there were relatively few investigations of larval OBPs in host plant recognition. Because most lepidopteran larvae graze directly on numerous crops, studying the roles of larval OBPs is critical.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Olfaction is vital in the transfer of chemical information and has long been studied by entomologists. OBPs are chemical signal recognition carriers, which are required for signal receiving while looking for food, mates, and so on. , Some studies reported that larvae can recognize certain pheromones, even sexual ones . However, there were relatively few investigations of larval OBPs in host plant recognition.…”
Section: Discussionmentioning
confidence: 99%